Mathematical Reasoning for Elementary Teachers - Calvin T. Long (Pearson, 2015)
Millman's Mathematical Reasoning for Elementary Teachers presents the mathematical content needed for teaching within the context of the elementary classroom, giving future teachers the motivation they need while also showing them the bigger picture of when they will use and teach the concepts. The program also endeavors to answer the frequently-asked "Why are we learning this?" by going beyond skill explanations and showing the ways that these concepts are implemented in the future classroom and what types of questions children may ask. Now updated to include the Common Core State Standards for Mathematics, the text imparts mathematical reasoning skills, a deep conceptual understanding, and a positive attitude to those who aspire to be elementary or middle school teachers.Teaching and Learning ExperienceThis program will provide a better teaching and learning experience-for you and your students. Here's how: Personalized learning with MyMathLab: MyMathLab delivers proven results in helping students succeed and provides engaging experiences that personalize learning. Features for the future classroom demonstrate the relevance of the concepts students are learning, the ways in which the mathematical concepts will be employed in the classroom, provide perspective on the importance of learning the material, and engage students to learn by doing. Strong pedagogical tools help students to understand and retain the essential principals.